The Impact of Digital Infrastructure Investment on Economic Growth and Social Inclusion in Emerging Economies - Durand Fernandito; Amin Sadiqin; Royya Huseynzadeh (International Forum of Researchers and Lecturers, 2024)
This study explores the significant role of digital infrastructure investments in driving both economic growth and social inclusion in emerging economies. With the rapid advancements in digital technologies such as broadband, mobile subscriptions, and ICT infrastructure, these investments are reshaping economies by fostering innovation, improving business efficiency, and reducing poverty. The research employs a quantitative cross-country panel data approach, examining the impact of digital infrastructure across various regions over a ten-year period. The findings reveal a strong positive correlation between digital infrastructure investments and GDP growth, highlighting the substantial effect these investments have on national economic performance. Additionally, the study demonstrates that digital infrastructure plays a pivotal role in enhancing social inclusion, particularly through improved access to financial services, education, and healthcare, which in turn reduces income inequalities and promotes social mobility. The paper also compares the impact of digital infrastructure with that of traditional investments in physical infrastructure, such as transportation, revealing that digital infrastructure offers higher returns in terms of both economic outcomes and social benefits. This research emphasizes the importance of policy interventions, including targeted subsidies and inclusive digital policies, to foster equitable growth. Finally, it proposes several directions for future research, including sector-specific impacts of digital infrastructure, regional disparities, and the long-term effects on social well-being.